2017
DOI: 10.1039/c7dt00329c
|View full text |Cite
|
Sign up to set email alerts
|

Gold setting the “gold standard” among transition metals as a hydrogen bond acceptor – a theoretical investigation

Abstract: The Au(i) atom of dimethylaurate (DMA) is shown to behave as a hydrogen-bond acceptor, providing theoretical evidence that it can act as a Lewis base. Calculations at the MP2/aug-cc-pVTZ-pp level of theory confirm that DMA forms hydrogen bonds decreasing in strength from -16.2 kcal mol to -2.4 kcal mol in the order HCN ≈ HF > HO > HCCH > NH > CH, i.e. following the trend of decreasing proton acidity of the hydrogen-bond donor. The geometrical and Atoms in Molecules (AIM) parameters of the hydrogen-bonded adduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 48 publications
2
32
0
2
Order By: Relevance
“…[2,3] More recently,t he interactions of gold complexes with hydrogen ligands have becomeafocus of discussion, andi np articulart he ability (or otherwise) of gold complexes to undergo hydrogen bonding has been am atter of debate. [4][5][6][7] For gold(I), with its completely filled d-shell,aseries of experimental and theoretical studies have demonstrated the presence of Au···HC interactions. [8][9][10] The nature of bonding in cases of closeAu···HN contacts between Au I and protonated Nbases in the crystal remained uncertain, since such contacts could simply be the consequence of crystal packing effects.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] More recently,t he interactions of gold complexes with hydrogen ligands have becomeafocus of discussion, andi np articulart he ability (or otherwise) of gold complexes to undergo hydrogen bonding has been am atter of debate. [4][5][6][7] For gold(I), with its completely filled d-shell,aseries of experimental and theoretical studies have demonstrated the presence of Au···HC interactions. [8][9][10] The nature of bonding in cases of closeAu···HN contacts between Au I and protonated Nbases in the crystal remained uncertain, since such contacts could simply be the consequence of crystal packing effects.…”
Section: Introductionmentioning
confidence: 99%
“…Only af ew recent examples are given that are not contained in the Review of 2014. [16,17] Optimized geometries have been calculated and bond strengths estimated. [15] Several theoretical investigations by Esterhuysen, Raubenheimer,a nd co-workers have provided new and complementary data [7] forh ydrogen-bonded aggregates of the auride anion [Au] À and of dialkylaurate(I) anions [RÀAuÀ R] À where strong electrostatic contributions should favor Au···H À Xbonding with strong hydrogen bond donors such as H 2 O, NH 3 ,HCN,oreven HF.…”
mentioning
confidence: 99%
“…[15] Several theoretical investigations by Esterhuysen, Raubenheimer,a nd co-workers have provided new and complementary data [7] forh ydrogen-bonded aggregates of the auride anion [Au] À and of dialkylaurate(I) anions [RÀAuÀ R] À where strong electrostatic contributions should favor Au···H À Xbonding with strong hydrogen bond donors such as H 2 O, NH 3 ,HCN,oreven HF. [16,17] Optimized geometries have been calculated and bond strengths estimated. Relativistic effects were shown to play adominant role in the formation of the hydrogen bonds,f or which the energy is correlated with the proton acidity of the donor molecules (16.0, 11.5, and 6.2 kcal mol À1 for dimethylaurate(I) with HF,H 2 O, and NH 3 , respectively).…”
mentioning
confidence: 99%
“…Ein bedeutsamer Beitrag aus jüngster Zeit von Schwerdtfeger et al ist der ungewçhnlich spezifischen Protonenaffinitätv on Gold-Koordinationszentren in ganz unterschiedlichen Ligandsphären gewidmet, die auf relativistische Effekte zurückgeht. [16,17] Die berechneten Molekülgeometrien entsprechen den Erwartungen, und die Wechselwirkungsenergien sind mit den Protonen-Aciditäten korreliert. [ R-Au-R] À ,i nd enen starke elektrostatische Beiträge die X-H···Au-Bindungen mit starken Donoren HX wie H 2 O, NH 3 ,H CN und sogar HF unterstützen kçnnen.…”
Section: Addendumunclassified
“…[ R-Au-R] À ,i nd enen starke elektrostatische Beiträge die X-H···Au-Bindungen mit starken Donoren HX wie H 2 O, NH 3 ,H CN und sogar HF unterstützen kçnnen. [16,17] Die berechneten Molekülgeometrien entsprechen den Erwartungen, und die Wechselwirkungsenergien sind mit den Protonen-Aciditäten korreliert. Fürdie Kombination von Dimethylaurat(I) mit HF,H 2 Ou nd NH 3 betragen die Werte 16.0, 11.5 bzw.6 .2 kcal mol À1 .S ie sind stark von relativistischen Effekten bestimmt, und deshalb werden fürdie Kupferund Silber-Analoga [R-M-R] À mit M = Cu, Ag wesentlich geringere Werte gefunden.…”
Section: Addendumunclassified